Long-term salinity development in a lysimeter experiment - van Hoorn I.W.; Katerji N.; Hamdy A. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
Over a period of 6 years, various crops were grown in tanks, filled with loam and clay, and were irrigated with water of three different levels of salinity. A combination of soil water sampling, salt balance and salt model was used to study the change in the composition of the soil water and the development of soil salinity. After 3 years an equilibrium was attained in the magnesium carbonate occurred during the whole experimental period. During the last two cropping periods the average chloride concentration of the soil profile obtained from soil water sampling was about twice as low as that obtained from the salt balance, due to preferential flow through macropores attaining the porous cups. Model calculation indicated a bypass fraction of a about 0.15. The steady-state leaching model of USSL could be used to estimate the long-term chloride concentration of the soil profile.